2020
DOI: 10.1111/wvn.12437
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acupressure on Acute Pain During Venipuncture in Children: Implications for Evidence‐Based Practice

Abstract: AimsThe study was conducted as a randomized controlled trial in order to determine the effects of acupressure on acute pain during venipuncture in children.MethodsThe population of the study consisted of children, aged between 9 and 12 years, who received venipuncture between September 2015 and June 2016 at a university hospital in Istanbul. The sample consisted of a total of 90 children, including 45 children in the acupressure group and 45 children in the control group, who met the sample inclusion criteria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Numerous studies in the literature detail the effect of acupressure on pain level following CA (3,6,11,(12)(13)(14). In a limited number of studies, it was stated that acupressure was applied within 24 h or more than once, and the immediate effect of acupressure applied once was examined (11,12,(15)(16)(17)(18). In previous studies, the LI4, LI11, and PC6 points were found to be the most commonly used points to reduce the pain level (11,12,(15)(16)(17)(18); however, no study has used them together or examined their effects on pain and hemodynamic parameters after CA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies in the literature detail the effect of acupressure on pain level following CA (3,6,11,(12)(13)(14). In a limited number of studies, it was stated that acupressure was applied within 24 h or more than once, and the immediate effect of acupressure applied once was examined (11,12,(15)(16)(17)(18). In previous studies, the LI4, LI11, and PC6 points were found to be the most commonly used points to reduce the pain level (11,12,(15)(16)(17)(18); however, no study has used them together or examined their effects on pain and hemodynamic parameters after CA.…”
Section: Introductionmentioning
confidence: 99%
“…In a limited number of studies, it was stated that acupressure was applied within 24 h or more than once, and the immediate effect of acupressure applied once was examined (11,12,(15)(16)(17)(18). In previous studies, the LI4, LI11, and PC6 points were found to be the most commonly used points to reduce the pain level (11,12,(15)(16)(17)(18); however, no study has used them together or examined their effects on pain and hemodynamic parameters after CA. Therefore, the aim of this study was to determine the effect of acupressure, which is one of the nonpharmacologic methods, on pain and hemodynamic parameters [systolic blood pressure (SBP), diastolic blood pressure (DBP), peripheral oxygen saturation (SpO 2 ), RR, and HR] in patients after CA.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of negative reactions in the control group was significantly higher than in the other groups (Table 2; P > 0.05). Özkan Koc and Balci 21 reported that there were no differences between the children (9 to 12) in the acupressure and control groups in terms of age, sex, presence of the parents during the venipuncture procedures, and number of venipunctures within the previous year.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding acupressure, numerous studies affirm the effectiveness of this nonpharmacological method in reducing pain intensity. Ozkan et al confirmed the efficacy of acupressure in reducing venipuncture pain in children [ 62 ]. Furthermore, Yildirim et al conducted a study on “The Effect of Acupressure on Vital Signs, Acute Pain, and Stress during Venipuncture” involving 200 patients in Istanbul.…”
Section: Discussionmentioning
confidence: 99%